KAJIAN KUALITAS AIR IRIGASI TALAWAAN SEBAGAI SUMBER AIR PERSAWAHAN DI DESA TALAWAAN KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA - Billy Fandy. Sagai; Sofia Wantasen; Annie E. arore (COCOS, 2020)
ABSTRACTWater has a very important role in life because all living things in this world need water.Plants and animals are mostly composed of water. Plant cells contain more than 75% waterand animal cells contain more than 67%. Less than 0.5% of water can be used directly forhuman purposes. Less than 0.5% of water can be used directly for human purposes. Thepurpose of this study was to determine the Talawaan irrigation water quality associated withSodium Adsorption Ratio (SAR) in Talawaan District, North Minahasa Regency. Talawaanirrigation water quality in Talawaan District includes SAR parameters in the TertiaryIrrigation Channel (1) of 1.56 me / L and SAR in Tertiary Irrigation Channels (2) of 0.92 me /L meets the requirements of irrigation water quality in the good category.Keywords: Water Quality, Sungai Talawaan, Irigation Water